SKYFITY: Bridging the Gap Between ASEAN and Korean Youth in Fostering ASEAN -Korea Partnership [SKYFITY: Menjembatani Gap Antara Anak Muda ASEAN dan Korea dalam Mengembangkan Kerja Sama ASEAN-Korea] - Aji, Helmy Yahya Rahma; Anindhita, Anissa Rosalin (Sekretariat Jenderal DPR RI, 2022)
ASEAN and Korea have been developing a close partnership in various fields involving many actors. However, there is a perception gap between the youth in ASEAN and Korea in which Korea is widely known by ASEAN youth but not vice versa. The perception gap between ASEAN and Korean is confirmed by various studies such as studies by Jin-pyo et al. and Ji-hyeon. Other study by Rosland also implies that Koreans are not really aware of ASEAN. Those studies indicate that there is a need of further cooperation to promote mutual understanding. However, they do not mention or propose a concrete idea to bridge the gap. Some efforts have been made to address this issue but they seem to be ineffective. In this paper, qualitative method is used to obtain data and more directed at this study case of perception gap. Data are obtained by searching for data through document review, whether from books, scientific journals, or any related documents. This paper proposes a new initiative named SKYFITY (ASEAN-Korea Youth Fraternity) to bridge this gap. This initiative employs cultural and public diplomacy approaches and emphasises the youth in ASEAN and Korea to participate and contribute in this initiative. SKYFITY comprises three actors; governmental (ASEAN and the Republic of Korea Government), external actors (private enterprises and cultural institutions) and the youth. SKYFITY encompasses social, culture and entrepreneurship dimensions to foster mutual understanding among youth in ASEAN and Korea.AbstrakASEAN dan Korea telah mengembangkan kerja sama yang dekat di berbagai bidang. Namun, masih terdapat perception gap antara anak muda ASEAN dan Korea; Korea dikenal secara luas oleh anak muda ASEAN, tetapi tidak dengan sebaliknya. Perception gap antara anak muda ASEAN dan Korea telah diperkuat oleh beberapa studi seperti studi oleh Jin-pyo et al. dan Ji-hyeon. Studi lain oleh Roslan juga menyiratkan bahwa masyarakat Korea kurang tahu mengenai ASEAN. Studi-studi tersebut mengindikasikan perlu adanya kooperasi untuk meningkatkan pemahaman bersama satu sama lain. Namun, studi-studi tersebut tidak menyebut atau mencanangkan langkah konkret untuk menjembatani gap ini. Beberapa usaha telah dilakukan untuk mengatasi persoalan ini, tetapi masih belum efektif. Esai ini menggunakan metode kualitatif dan diarahkan pada studi kasus mengenai studi kasus gap persepsi ini. Data diperoleh dengan pencarian melalui dokumen, seperti buku, artikel jurnal, atau dokumen lainnya yang berhubungan. Esai ini menawarkan sebuah inisiatif yang Bernama SKYFITY (ASEAN Korea Youth Fraternity) untuk menjembatani gap tersebut. Inisiatif ini menggunakan pendekatan diplomasi budaya dan public yang menekankan anak muda di ASEAN dan Korea untuk ikut serta dan berpartisipasi dalam inisiatif ini. SKYFITY terdiri dari tiga aktor; pemerintah (pemerintah ASEAN dan Republik Korea), eksternal (swasta dan institusi budaya) dan anak muda. SKYFITY meliputi dimensi sosial, budaya, dan kewirausahaan untuk meningkatkan pemahaman satu sama lain antara anak muda di ASEAN dan Korea.